The sharing of macroeconomic risk. Who loses (and gains) from macroeconomic shocks - Ahrend, Rudiger; Arnold, Jens; Moeser, Charlotte (Paris, 2011)
"This paper addresses the often neglected question of how macroeconomic risk is shared across and within economies, and identifies reforms that could contribute towards achieving more desirable risksharing outcomes. For risk-sharing across countries, the paper discusses possibilities for international insurance as well as shock-spreading and risk-mitigating policies. Within countries, it assesses the possibilities for individuals to protect their wealth, labour and capital income against various forms of macroeconomic risk and discusses the desirable boundaries between private and government-sponsored risk-sharing institutions. The paper then presents new empirical and model-based evidence about how the short-term impact of selected macroeconomic shocks (including financial crises) is shared across different groups of agents, and analyses how such distributional effects are shaped by differences in institutions. For example, individuals on low incomes, and especially young people, seem in general to lose most from adverse macroeconomic shocks. Also, it appears that across countries two broad types of institutions can be identified that facilitate risk sharing between high and low income earners, namely "social protection" and "reallocation-facilitating" institutions. Based on countries’ reliance on these types of institutions, four broad "models" of risk sharing are identified across the OECD and the BRIICS."